The Cambridge introduction to George Eliot - Henry, Nancy (Cambridge University, 2013)
George Eliot was one of the most admired novelists of the Victorian period. This introduction provides students with the religious, political, scientific and cultural contexts they need to understand and appreciate her novels, stories, poetry and critical essays. Nancy Henry also traces the reception of her works.